ENGLISH AND INDONESIAN LETTER-WRITING (Universitas Muhammadiyah Palembang, 2023)
This research is aimed at figuring out the similarities, dissimilarities, and its contribution to TEFL. The qualitative research method was used. To collect the data, the researchers used documentation technique. There were 18 students of English Department of Universitas PGRI Palembang as the subject of this research. To analyze the data, the researchers used qualitative analysis. The findings revealed 4 similarities in heading, salutation, complementary close and signature and 2 dissimilarities in salutation and body of the letter based on the theoretical analysis. Also 5 similarities in heading, salutation, body of the letter, complementary close and signature and 2 dissimilarities in heading and body of the letter based on students’ writing exercises of English and Indonesian letter-writing in Job application letter. In brief, these findings can be utilized to develop teaching materials and supplemental resources in teaching writing.